Changes in diatom productivity and upwelling intensity off Peru since the Last Glacial Maximum: Response to basin‐scale atmospheric and oceanic forcing. (29th October 2016) - Doering, Kristin; Erdem, Zeynep; Ehlert, Claudia; Fleury, Sophie; Frank, Martin; Schneider, Ralph
Abstract: New records of stable silicon isotope signatures (δ 30 Si) together with concentrations of biogenic opal and organic carbon from the central (9°S) and northern (5°S) Peruvian margin reveal changes in diatom productivity and nutrient utilization during the past 20, 000 years. The findings are based on a new approach using the difference between the δ 30 Si signatures of small (11–32 µm) and large (>150 µm) diatom fractions (Δ 30 SiCoscino‐bSi ) in combination with the variance in diatom assemblages for reconstruction of past upwelling intensity. Combination of our records with two previously published records from the southern upwelling area off Peru (12–15°S) shows a general decoupling of the environmental conditions at the central and southern shelf mainly caused by a northward shift of the main upwelling cell from its modern position (12–15°S) toward 9°S during Termination 1. At this time only moderate upwelling intensity and productivity levels prevailed between 9°S and 12°S interpreted by a more northerly position of Southern Westerly Winds and the South Pacific Subtropical High. Furthermore, a marked decrease in productivity at 12–15°S during Heinrich Stadial 1 coincided with enhanced biogenic opal production in the Eastern Equatorial Pacific, which was induced by a southward shift of the Intertropical Convergence Zone and enhanced northeasterly trade winds. Modern conditions were only established at the onset of the Holocene. Past changes in preformed δ 30 Si signatures of subsurface waters reaching the Peruvian Upwelling System did not significantly affect the preserved δ 30 Si signatures. Key Points: Combined silicon isotope signatures and diatom assemblages trace productivity and upwelling intensity Latitudinal shifts of Peruvian upwelling center mainly responded to movements of the SWW and ITCZ Isotopic compositions of upwelled subsurface waters off Peru not significantly influenced by changes in preformed nutrients